Young Danube delta documents stable Black Sea level since the middle Holocene: Morphodynamic, paleogeographic, and archaeological implications - Giosan, L.; Donnelly, J. P.; Constantinescu, S.; Filip, F.; Ovejanu, I.; Vespremeanu-Stroe, A.; Vespremeanu, E.; Duller, G. A. T. (Geology, 2006)
New radiocarbon and optical dates show that the Holocene Danube delta started to build out of a Black Sea embayment similar to 5200 yr ago. Delta lobe development phases differ by as much as 5 k.y. from previously proposed ages. The new chronology allows for a better understanding of the Danube delta paleogeography, including the demise of Istria, the main ancient Greek-Roman city in the region. Prior reconstructions of sea level in the Black Sea inferred fluctuations to 15 m in range; however, stratigraphy of beach ridges in the delta shows that the relative Black Sea level for the past 5 k.y. was stable in the Danube delta region within -2 m and +1.5 of the current level. Hydroisostatic effects related to a proposed catastrophic reconnection of the Black Sea to the World Ocean in the early Holocene may have been responsible for the sea level reaching the highstand earlier than estimated by models. The new sea-level data suggest that submergence at several ancient settlements around the Black Sea may be better explained by local factors such as subsidence rather than by basin-wide sea-level fluctuations.
084aqTimes Cited:63Cited References Count:35